HCV and HIV binding lectin, DC-SIGNR, is expressed at all stages of HCV induced liver disease. Issue 1 (23rd December 2003) - Cole, G; Coleman, N; Soilleux, E
Abstract : The process by which hepatitis C virus (HCV) enters cells and the reason for its hepatotropism remain obscure. Recently, the human immunodeficiency virus (HIV) binding lectins, DC-SIGN and DC-SIGNR, were shown to bind HCV. This article reports the expression of DC-SIGN and DC-SIGNR in HCV related liver disease and discusses whether these lectins, in particular DC-SIGNR, are responsible for HCV hepatotropism.